Development of the closed loop pulsating heat pipe cool roof system for residential buildings - L.H. Saw; M.C. Yew; M.K. Yew; W.T. Chong; H.M. Poon; W.S. Liew; W.H. Yeo (Case Studies in Thermal Engineering, 2021)
In tropical countries, air conditioning system is commonly used to provide thermal comfort in buildings. However, operating the air-conditioning system for long hours daily will result in escalating electricity bill. Hence, an effective roof cooling system is desired to reduce the high energy cost while maintaining the thermal comfort in the buildings. In view of this, closed loop pulsating heat pipe (CLPHP) roof cooling system is introduced in this study. The thermal performances of the CLPHP roof system are investigated through a series of experiments and benchmark with the bare metal roof system design. The experiment results showed that the cool roof system with CLPHP technology can lower the attic temperature from 34 °C to 29.6 °C, with about 13% of temperature reduction as compared to the bare metal roof design. The results showed that CLPHP cool roof system is found to be a promising method for attic retrofitting interventions to improve thermal comfort in the building.